Forty years (1978-2018) of vaccination policies in Italy - Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
The paper traces the evolution of vaccination policies in Italy in the first 40 years of the National Health Service. Four phases have been identified: the first (1978-98) characterized by the eradication of smallpox, the hopes of further eradications and the introduction of hepatitis B and acellular antipertussis vaccines; the second (1999-2008) coincided with the first national vaccination plans and with the hypothesis of a progressive transition from mandatory vaccinations to nudging initiatives with the relevant experimentation in the Veneto Region; the third phase (2009-14) was characterized by the spread of health information on the web and social networks, by anti-scientific judgments and by an increasingly vaccines hesitancy that led to incorrect perceptions, falls in coverage rates and re-ignition of some epidemics; in the last phase (2015-18) there was a strong political committment that led to the approval of the National Plan (PNPV) 2017-19, to the extension of the mandatory vaccinations and to the sanctions against the anti-vaxxers doctors. This has led to a rapid rise in coverage, but also to a heated political and media debate on the ethical and social aspects linked to the admission bans and sancions of unvaccinated children in schools.